Pengaruh Implementasi Aplikasi Kewirausahaan Terhadap Produktivitas Usaha Mikro, Kecil dan Menengah (UMKM) - Rafky Ferdian Algiffari; Lintan Amalliyah Putri; Arsil Mujayanah; Ahmad Fahmi Abdillah; Perani Rosyani (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Micro, small, and medium enterprises are the largest economic actors in the Indonesian economy. They are the primary source of state income, one of which is the Indonesian state. Micro, small, and medium enterprises can create many entrepreneurs and open many jobs to become the business sector that contributes the most to national development. This study used a quantitative approach. The instrument used is a questionnaire. The result of this study is that the implementation of entrepreneurial applications is proven to increase the productivity of the micro, small, and medium enterprises sector of tegal stalls, pecel lele, solo iced tea, padang restaurants, fried rice, laundry services, motorcycle washing services, coffee shops, ngodeng, and geprek chicken substantially with an average percentage increase of 29.3%. To increase the productivity and efficiency of micro, small, and medium enterprises, it can utilize the application of entrepreneurship effectively and directly influence micro, small, and medium enterprises. The positive influence on micro, small, and medium enterprises can enjoy various advantages from using entrepreneurial applications. The implementation of entrepreneurial applications can be done using the website to improve service quality and expand customer networks.